Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Landscape configurations with greater seminatural habitat and edge density enhance soybean yield across multiple spatial scales - Leonardo D. Amarilla; Gabriel Grilli; Daihana S. Argibay; Agustín Vargas Clérico; Pablo Y. Huais; Mariana P. Mazzei; Nicolás Szawarski; Carolina Torres; Matías Maggi; José L. Vesprini; Leonardo Galetto (Field Crops Research, 2025)

Urbanization weakens mutualisms without affecting antagonisms of a hawkmoth-pollinated plant species - Florencia Soteras; Silvana Longo; Noelia Cofré; M. Laura Bernaschini; Nicolás Marro; Julia Rodríguez; Santiago Costas; Adrián Giaquinta; Andrea A. Cocucci; Corina Vissio; Pablo Yair Huais; Gabriel Grilli (Urban Forestry & Urban Greening, 2025)

From nutrition to protection: the role of arbuscular mycorrhizal fungi in the interactions of plants with endoparasitic nematodes – A meta-analysis - Milena Caccia; Gabriel Grilli; Martina Janoušková; Nicolás Marro (Plant and Soil, 2025)

Soil cropping selects for nutrient efficient but more costly indigenous mycorrhizal fungal communities - Paula A. Buil; Jan Jansa; Martin Rozmoš; Michala Kotianová; Petra Bukovská; Gabriel Grilli; Nicolás Marro; Martina Janoušková (Biology and Fertility of Soils, 2025)
Conventional agriculture has been suggested to promote less mutualistic arbuscular mycorrhizal fungi (AMF). The main aim of this study was to test this assumption by a detailed functional analysis of the plant mycorrhizal benefits and costs. A cross-inoculation experiment was established with Plantago lanceolata as a host plant and inocula of AMF sourced from four pairs of conventionally managed arable fields and neighbouring grasslands. Mycorrhizal effects were determined for a range of plant parameters including fluxes of isotopically labelled phosphorus (P), nitrogen (N) and carbon (C), and related to root colonization and composition of the different AMF communities. The association of P. lanceolata with arable-field inocula was less beneficial in terms of plant growth promotion and it also led to more pronounced P accumulation in plant biomass, as compared to grassland inocula. Furthermore, arable-field AMF increased 15 N depletion in soil and 15 N transfer to shoots, and induced higher 13 C drain to soil. These differential functional parameters were related to consistent compositional differences between arable-soil and grassland AMF communities in the roots. Differential effects of the AMF inocula on N and C partitioning in the soil–plant system suggest faster foraging for nutrients by arable-soil AMF and higher demand for C, which are characteristics associated with ruderal AMF. This implies that arable-soil AMF may be less beneficial in conditions of plant growth limitation by C than the grassland AMF.

Morphological spore-based characterisation and molecular approaches reveal comparable patterns in glomeromycotan communities - Noelia Cofré; Gabriel Grilli; Nicolás Marro; Martín Videla; Carlos Urcelay (Mycorrhiza, 2025)

Pollinators significantly enhance seed set, yields and chemical parameters of oil seed in sunflower crops - Leonardo D. Amarilla; Gabriel Grilli; Pablo Y. Huais; Diana Labuckas; Damián Maestri; Mauro Ferrarese; Elian Tourn; Nicolás Szawarski; Gisela Grandinetti; María Florencia Ferreira; Carolina Torres; José L. Vesprini; et al. (Field Crops Research, 2025)

Impacts of mass flowering soybean on bee visitation rates of forest plants at different spatial scales - Pablo Yair Huais; Gabriel Grilli; Leonardo Galetto (Landscape and Urban Planning, 2024)

Low specificity and high variability of ectomycorrhizal association in Salix humboldtiana along its southern latitudinal distribution - Magali Burni; Silvana Longo; Gabriel Grilli; Eduardo Nouhra (Symbiosis, 2023)

Shifts from conventional horticulture to agroecology impacts soil fungal diversity in Central Argentina - Gabriel Grilli; Noelia Cofré; Nicolás Marro; Martín Videla; Carlos Urcelay (Mycological Progress, 2023)

Environmental response of arbuscular mycorrhizal fungi under soybean cultivation at a regional scale - Valeria Soledad Faggioli; Fernanda Covacevich; Gabriel Grilli; Claudio Lorenzon; Bethania Aimetta; Monica Sagadin; Adrián Langarica-Fuentes; Marta Noemí Cabello (Mycorrhiza, 2022)

Root-associated fungi increase male fitness, while high simulated herbivory decreases indirect defenses in Croton lachnostachyus plants - Mariana Pereyra; Gabriel Grilli; Leonardo Galetto (Plant Ecology, 2019)

The composition of arbuscular mycorrhizal fungal communities in the roots of a ruderal forb is not related to the forest fragmentation process - Gabriel Grilli; Carlos Urcelay; Leonardo Galetto; John Davison; Martti Vasar; Ülle Saks; Teele Jairus; Maarja Öpik (Environmental Microbiology, 2015)
Summary Land‐use changes and forest fragmentation have strong impact on biodiversity. However, little is known about the influence of new landscape configurations on arbuscular mycorrhizal fungal ( AMF ) community composition. We used 454 pyrosequencing to assess AMF diversity in plant roots from a fragmented forest. We detected 59 virtual taxa ( VT ; phylogenetically defined operational taxonomic units) of AMF – including 10 new VT – in the roots of E uphorbia acerensis . AMF communities were mainly composed of members of family G lomeraceae and were similar throughout the fragmented landscape, despite variation in forest fragment size (i.e. small, medium and large) and isolation (i.e. varying pairwise distances). AMF communities in forest fragments were phylogenetically clustered compared with the global, but not regional and local AMF taxon pools. This indicates that non‐random community assembly processes possibly related to dispersal limitation at a large scale, rather than habitat filtering or biotic interactions, may be important in structuring the AMF communities. In this system, forest fragmentation did not appear to influence AMF community composition in the roots of the ruderal plant. Whether this is true for AMF communities in soil and the roots of other ecological groups of host plants or in other habitats deserves further study.

Forest fragment size and nutrient availability: complex responses of mycorrhizal fungi in native–exotic hosts - Gabriel Grilli; Carlos Urcelay; Leonardo Galetto (Plant Ecology, 2012)